The Impact of Penicillin Skin Testing on Aztreonam Stewardship and Cost Savings in Immunocompromised Cancer Patients. (23rd August 2019) - Foolad, Farnaz; Berlin, Sheila; White, Candice; Dishner, Emma; Jiang, Ying; Taremi, Mahnaz
Abstract: Objective: Reported penicillin allergies result in alternative antimicrobial use and are associated with worse outcomes and increased costs. Penicillin skin testing (PST) has recently been shown to be safe and effective in immunocompromised cancer patients, yet its impact on antimicrobial costs and aztreonam utilization has not been evaluated in this population. Method: From September 2017 to January 2018, we screened all admitted patients receiving aztreonam. Those with a self-reported history of possible immunoglobulin E (IgE)-mediated reaction to penicillin were eligible for PST with oral challenge. Results: A total of 129 patients were screened, and 49 patients were included and underwent testing. Sixteen patients (33%) had hematologic malignancies and 33 patients (67%) had solid tumors. After PST with oral challenge, 46 patients (94%) tested negative, 1 patient tested positive on oral challenge, and 2 patients had indeterminate results. The median time from admission to testing was 2 days (interquartile range, 1–4). After testing negative, 33 patients (72%) were switched to beta-lactam therapy, which resulted in a total of 390 days of beta-lactam therapy. For identical therapy durations, the direct total antibiotic cost was $15 138.89 for beta-lactams versus $78 331.50 for aztreonam, resulting in $63 192.61 in projected savings. A significant reduction in median days of aztreonam therapy per 1000 patient days (10.0 vs 8.0; P = .005) was found during the intervention period. Conclusions: Use of PST in immunocompromised cancer patients receiving aztreonam resulted in improved aztreonam stewardship and significant cost savings. Our study demonstrates that PST with oral challenge should be considered in all cancer patients with reported penicillin allergies. Abstract : Among immunocompromised cancer patients with reported penicillin allergies, 94% tested negative on skin allergy testing with oral challenge; of these, 72% were transitioned to beta-lactam therapy, leading to significant cost savings and a reduction in institutional aztreonam use.